Contour optimization of a pin insulator using neural network - Aimua, Fidelis (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
ABSTRACT: Insulator geometry strongly affects the distribution of electric field along the surface of the insulator. If the field distribution is not uniform, that stresses the insulator unevenly which most often may lead to unnecessary loss of energy, flashover and eventual breakdown of the power network system. As the desire to have a more efficient, effective and reliable system devoid of losses increases; the need for a well optimized insulator arises. In this study, neural network is used to obtain an optimized form of a pin insulator. Neural network is trained by using geometric information of the pin insulator and field intensities in order to provide a field distribution as uniform and minimum as possible along the insulator surface. Electric field intensities along the surface for different insulator profiles are obtained numerically by using finite element method. Finally, the result obtained such as the mean absolute error of less than 0.1 at optimum, shows that the network has successfully been used to optimize the contour geometry of the pin insulator. Keywords: High voltage, insulator, contour optimization, neural network, electric field distribution. ………………………………………………………………………………………………………………………… ÖZ: İzolatör geometirisi, izolator yüzeyindeki elektrik alan dağılımını büyük oranda etkiler. Eğer izolatör yüzeyinde elektrik alan dağılımı düzgün değilse, izolatör zorlanır; bu durum genellikle güç sisteminde gereksiz enerji kaybına, atlamaya ve zamanla delinmeye yol açabilir. Daha verimli, etkin ve güvenilir kayıpsız bir sistem ihtiyacı arttıkça, optimum izolatör ihtiyacı da artar. Bu çalışmada, bir mesnet izolatörünün optimizasyonu için yapay sinir apı kullanılmıştır. Yapay sinir ağı, izolatörün geometrik bilgileri ve alan şiddetleri kullanılarak mümkün oladuğu kadar düzgün ve düşük şiddetli alan dağılımı sağlayacak şekilde eğitilmiştir. Farklı izolatör biçimleri için yüzey boyunca elektrik alan şiddetleri, sonlu elemanlar yöntemi kullanılarak sayısal olarak elde edilmiştir. Elde edilen sonuç, % 0,1 ortalama mutlak hata ile, sinir ağının mesnet izolatörü optimizasyonunda başarılı olduğunu göstermektedir. Anahtar Kelimeler: Yüksek gerilim, izolatör, biçim optimizasyonu, yapay sinir ağı, elektrik alan dağılımı.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2015. Supervisor: Assist. Prof. Dr. Suna Bolat.
Keywords: Electrical and Electronic Engineering; Electric insulators and insulation - Electric power distribution - High tension; Electric cables - Insulation; High Voltage, Insulator, Contour Optimization, Neural Network, Electric Field Distrubution